(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The production of national clothing is not only a way to preserve cultural heritage but also an important sector in the fashion and textile industry. Developing effective business strategies is crucial for ensuring the success and sustainability of traditional clothing production. This paper explores key aspects of national clothing manufacturing, including material selection, design innovation, production processes, and market positioning. Additionally, it examines business strategies such as branding, digital marketing, and international expansion that can help increase the global appeal of traditional clothing. By integrating modern fashion trends with traditional craftsmanship, businesses can attract a broader audience while preserving cultural authenticity.